Sejarah Hukum Perkawinan Sebelum dan Sesudah Lahirnya Undang-Undang Perkawinan - Muhamad Farid Alfurqon; Zahwa Amalia Fitri; Edi Mufrodi; Mohammad Rafi Padillah; Humaeroh Humaeroh (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
This research is motivated by the existence of legal pluralism in marriage regulations in Indonesia before the enactment of Law Number 1 of 1974 concerning Marriage. During that period, marriage provisions were influenced by various legal systems, namely customary law, Islamic law, and colonial laws such as the Burgerlijk Wetboek, whose application was based on population classification. This condition gave rise to various problems, including legal uncertainty, differing standards for marriage validity, and weak protection of the rights of women and children. Based on these problems, this study aims to examine the development of marriage law in Indonesia, both before and after the enactment of the Marriage Law, and to assess the extent to which these regulations have been able to achieve legal unification and certainty within the national legal system. The method used is qualitative-normative research with a literature study approach through analysis of relevant laws and regulations, historical documents, and scientific literature. The results indicate that before 1974, the marriage legal system was complex and unintegrated, necessitating a comprehensive codification. The process of drafting this law was lengthy and marked by ideological debate and religious considerations. However, an agreement was ultimately reached that accommodated both religious values ​​and state interests. Subsequent developments, including amendments through Law Number 16 of 2019, confirm that marriage law in Indonesia is dynamic in responding to demands for justice, human rights, and gender equality.